Price Competitiveness in Central and Eastern Europe - a case study for transition economies - Dominique Peters (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2010)
Newly industrialized countries and transition economies are often perceived as a threat to Western countries in public discussion, and concerns about economic 'competitiveness' arise. The present paper focuses on the specific macro-economic term 'price competitiveness'. It analyzes the underlying assumptions of the term, explainshow the 'price competitiveness' indicator is composed, and what the restrictions arewhen applying it to transition economies. When calculating the 'price competitiveness' indicator for Central and Eastern European New Member States of the European Union in the last decade, all ten countries show values that are conventionally understood as a steady 'loss in price competitiveness'. Still, this has not led to lower export growth in the last decade in these countries. Instead, all ten assessed countries show above-average growth in Exports, in Manufacturing goods, and in Gross Domestic Product, compared to the rest of the world.The 'price competitiveness' indicator fails, due to inherent assumptions and technical implications, to explain the Export development in economies that are fastgrowing and going through a process of industrialization - so called 'catch-up economie' - what has been the case in the Central and Eastern European countries in the last decade. The 'price competitiveness' indicator should thus not be applied irrespectively of a country's economic situation.
urn:nbn:de:101:1-201101312985
Keywords: 330; Preiswettbewerb; Internationaler Wettbewerb; Übergangswirtschaft; Entwicklungskonvergenz; EU-Mitgliedschaft